Tentative detection of some alkyl coumarates and alkyl ferulates in lpomoea carnea subsp. fistulosa by HRESIMS and comparison of these compounds among Convolvulaceae plants - J Nidiry, Eugene Sebastian (Pharmacognosy Communications)
Three alkyl coumarates (hexadecyl coumarate, eicosyl coumarate and docosyl coumarate) and five alkyl ferulates (tetradecyl ferulate, pentadecyl ferulate, heptadecyl ferulate, octadecyl ferulate and nonadecyl ferulate) could be tentatively detected in the partially purified HPLC fraction of Ipomoea carnea subsp. fistulosa by high resolution electrospray ionization mass spectroscopy (HRESIMS). This is in addition to octadecyl p-coumarate whose detailed structure elucidation, antifungal activity and isomerization have already been reported. The compounds were compared with alkyl coumarates and alkyl ferulates reported from other Convolvulaceae plants. It was found that octadecyl p-coumarate is the most frequently reported alkyl coumarate in the family. It was also observed that while the number carbon atoms in the alkyl groups of alkyl coumarates reported from Convolvulaceae is always even, in the case of alkyl ferulates, number of carbon atoms of the alkyl moiety can either be odd or even.
Keywords: Ipomoea carnea subsp. fistulosa; alkyl coumarates; alkyl ferulates; Convolvulaceae; HRESIMS